Retensi Nitrogen dan Konversi Pakan Ayam Lokal Persilangan yang Diberi Ekstrak Umbi Dahlia (Dahlia variabilis) sebagai Sumber Inulin - A. F. Fanani; N. Suthama; B. Sukamto (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
The research was aimed to evaluate used dahlia tubersextract as inulinsource onnitrogen retention and feed conversion of crossbred local chicken (male native chicken × female laying hen). Three weeks old 160 unsex birds with average body weight 180.46±1.21g were kept until 8 weeks. The experimentwas designed ascompletely randomized design with 4 treatments and 4 replications (@10 birds). Treatments applied were T0: basal ration, T1: ration + 0.39% extract, T2: ration + 0.78% extract, T3: ration + 1.17% extract. Parameters observed werenitrogen retention, energy metabolism and feed conversion. The data were statistically analyzed according to ANOVA and continued by Duncan test at the level of 5%. The results showed that feeding dahlia tuberextract significantly affect (P<0.05) nitrogen retentionwith value T0-T3 (1.3g, 1.47g, 1.43g, 1.7g)and feed conversion (4.15, 3.58, 3.75, 3.47), but not significant of energy metabolism. In conclusion, the higher levels of feeding inulin in the form of extract in T3 (1.17%), increase nitrogen retention and improve feed conversionof crossbred local chicken.